IPTEKS PENINGKATAN KINERJA KARYAWAN PADA PT. BURSA EFEK INDONESIA KANTOR PERWAKILAN SULAWESI UTARA - Dolontelide, Claudia Meygriza; Latjandu, Lady D. (Universitas Sam Ratulangi, 2018)
Job satisfaction will affect employee performance. Employees with high job satisfaction can produce maximum work performance. Conversely, employees with low job satisfaction will produce bad work performance. Therefore, job satisfaction is one of the important factors in a company that needs attention from the company's leadership. The science and technology method used is six dimensions in job satisfaction stated by Luthans (2006) which consists of the work itself, salary or wages, opportunities for promotion, supervision, work colleagues and working conditions. This study serves to measure job satisfaction and how it affects to employee performance at PT. Indonesia Stock Exchange North Sulawesi Representative Office.Keywords: job satisfaction, employee performance, dimensions in job satisfaction